(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Most studies emphasize the psychosomatic genesis of the pathology of the digestive tract, which is based on stress, which triggers the mechanism of formation of functional and organic pathology through a cascade of vegetative reactionsA study of the clinical and epidemiological features of tuberculosis of extrapulmonary localizations in Uzbekistan for the period from 2020 to 2023 was conducted.